Subtitling cultural expressions in “Barbie” movie into Arabic - Obeidat, Mohammed M.; Abbadi, Rawda A. (Research Journal in Advanced Humanities, 2024)
The current study aims to investigate the most used strategies in audiovisual translation, namely, subtitling different types of English culture-bound expressions into Arabic. Furthermore, this study aims to determine the most frequent cultural expressions and the subtitling strategies used to translate their meaning from English into Arabic. The data of this research is extracted from the American fantasy-comedy movie Barbie “باربي,” which was released on July 21, 2023. Numerous websites offer streaming access to the film. The online source from which the English subtitles were sourced is Shofha TV “تي في شوفها.” The research’s data was analyzed using Gottlieb’s (1992) subtitling strategies. The Arabic subtitles of these cultural expressions were compared to their English equivalents to check the adequacy of translation and comprehensibility. According to the study, paraphrase, transfer, deletion, expansion, condensation, resignation, decimation, and imitation are the most employed strategies. In addition, this study shows that the most frequent culture-specific expressions taken from Barbie movies are slang expressions, taboos, idioms, and religious expressions. The study concludes that paraphrase (30%), transfer (19%), deletion (15%), and expansion (11%) were the most frequent subtitling strategies used to deal with English cultural expressions.